Environmental Security in Harbors and Coastal Areas Management Using Comparative Risk Assessment and Multi-Criteria Decision Analysis - Linkov, Igor.; Kiker, Gregory A.; Wenning, Richard J.; SpringerLink (Online service) (Dordrecht : Springer Netherlands : Imprint: Springer, 2007)
Human experience has shown how great cities, nations, and empires have either collapsed or retired from their predominant stature when natural resources are depleted to an extent that exceeds the ability of the environment to restore or replenish their supply. This book explores the challenges facing coastal areas during the next few decades and the difficult decisions needed to prevent a repeat of the past. Establishing, maintaining or enhancing a sense of environmental security in different coastal regions and improving the management of critical infrastructure will require (i) matching human demands with available environmental resources; (ii) recognition of environmental security threats and infrastructure vulnerabilities; and, (iii) identification of the range of available options for preventing and/or minimizing natural disasters, technological failures, and/or terror actions. This book emphasizes beliefs that the convergence of seemingly disparate viewpoints and often uncertain and limited information is possible only by using one or more available risk assessment methodologies and decision-making tools such as multi-criteria decision analysis (MCDA).
Environmental Security: Regulatory Needs and Tools -- ENVIRONMENTAL SECURITY, CRITICAL INFRASTRUCTURE AND RISK ASSESSMENT -- ENVIRONMENTAL SECURITY -- INTEGRATING COMPARATIVE RISK ASSESSMENT AND MULTICRITERIA DECISION ANALYSIS -- ENVIRONMENTAL SECURITY IN HARBORS AND COASTAL AREAS -- Coastal Areas: Challenges and Solutions -- ENVIRONMENTAL SECURITY AND ENVIRONMENTAL REGULATIONS IN ISRAEL -- MANAGING SEDIMENT RISK AT THE BASIN SCALE -- MULTICRITERIA DECISION ANALYSIS AND STRATEGIC UNCERTAINTIES -- RANKING OF AVAILABLE COUNTERMEASURES USING MCDA APPLIED TO CONTAMINATED ENVIRONMENT -- ENGAGING THE GENERAL PUBLIC AND OTHER STAKEHOLDER GROUPS -- RISK AND DECISION METHODS APPLIED TO AQUATIC ECOSYSTEM MANAGEMENT -- STAKEHOLDER PREFERENCE ELICITATION -- MULTIOBJECTIVE RISK/COST ANALYSIS OF ARTIFICIAL MARINE SYSTEMS USING DECISION TREES AND FUZZY EXPERT ESTIMATIONS -- THE BOUCHARD-120 AND CHALK POINT SPILL RESPONSES: OBJECTIVES AND PERFORMANCE METRICS -- Applications of Multi-Criteria Decision Analysis -- COMPARATIVE ASSESSMENT OF SEVERAL MULTI-CRITERIA DECISION ANALYSIS TOOLS FOR MANAGEMENT OF CONTAMINATED SEDIMENTS -- SMAA-TRI -- COMPARATIVE ASSESSMENT OF SEVERAL MULTI-CRITERIA DECISION ANALYSIS TOOLS FOR MANAGEMENT OF CONTAMINATED SEDIMENTS -- FUZZY VS. PROBABILISTIC METHODS FOR RISK ASSESSMENT OF COASTAL AREAS -- DECISION SUPPORT SYSTEMS FOR THE MANAGEMENT OF CONTAMINATED SITES -- VISUALIZATION OF PARETO FRONTIER IN ENVIRONMENTAL DECISION MAKING -- SPATIALLY-EXPLICIT POPULATION MODELS WITH COMPLEX DECISIONS -- Applications of Risk Assessment -- RISK ASSESSMENT IN DETECTION AND PREVENTION OF TERRORIST ATTACKS IN HARBORS AND COASTAL AREAS -- COMPLEX HEALTH RISK ASSESSMENT AND ANALYSIS FROM EXPOSURE TO IONIZING RADIATION, CHEMICAL CONTAMINANTS AND OTHER SOURCES OF HARM -- ROLE OF RISK ASSESSMENT IN ENVIRONMENTAL SECURITY PLANNING AND DECISION-MAKING -- HUMIC SUBSTANCES AS A NATURAL FACTOR LOWERING ECOLOGICAL RISK IN ESTUARIES -- RISK ASSESSMENT APPLICATIONS IN CROATIA -- Case Studies in Environmental Security Analysis -- RISK ASSESSMENT OF THE EFFECT OF WASTEWATER TREATMENT AND DESALINATION PROCESSES ON THE COASTAL AQUIFER IN ISRAEL -- EVALUATION OF DRINKING GROUNDWATER FOR THE RURAL AREAS ADJACENT TO THE NEARBY DESERT OF GIZA GOVERNORATE OF GREATER CAIRO, EGYPT -- IMPACT OF LITHUANIAN SEA HARBORS ON ENVIRONMENTAL STABILITY AND LOCAL ECOSYSTEMS -- THE CASPIAN SEA REGION -- INVESTIGATION OF DISCHARGE OF FRESH WATER IN THE CANAKKALE STRAIT (DARDANELLES -TURKEY) -- THE SOUTH MEDITERRANEAN COASTAL SUSTAINABLE DEVELOPMENT PROJECT -- LAKE SEVAN IN ARMENIA -- MULTI-CRITERIA DECISION ANALYSIS AND THE TAR CREEK SUPERFUND SITE -- UNMANNED SEA VEHICLES FOR HARBOR PATROLLING.
Keywords: Environmental management; Oceanography; Coasts; Operations research; Decision making; Environmental economics; Environmental sciences; Environmental Management; Oceanography; Coastal Sciences; Operations Research/Decision Theory; Environmental Economics; Math. Appl. in Environmental Science